Analisis Rantai Pasok dan Nilai Tambah Karet di PT Andalas Agrolestari Kabupaten Kuantan Singingi Provinsi Riau - Ningsih, Arum Rovarti; Hamzah, Farida Hanum; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This research aims to analyze the flow of supply chain and added value of rubber and determined the priority of supply chain strategies at PT. Andalas Agrolestari. This study was conducted at PT. Andalas Agrolestari Kuantan Singingi District Riau Province. The research methods used were qualitative descriptive and quantitative descriptive. The respondents in this study consisted 3 farmers, 2 collectors, 3 employees of PT. Andalas Agrolestari, 2 civil servants of Agriculture Department, and Singingi sub-district head. This research showed the supply chain of rubber at PT. Andalas Agrolestari in Kuantan Singingi included farmers, collectors, PT. Andalas Agrolestari to consumers. Value added farmer was 1,037 IDR and included in the value added ratio of 55% (high category), collector was 448 IDR with the value added ratio of 5% (low category), and PT Andalas Agrolestari was 4,223 IDR with the value added ratio of 30% (medium category). The internal factor evaluation matrix has a total score of 2.5440, while the external factor evaluation matrix has a total score of 2.4128. The results of the supply chain management strategyat PT. Andalas Agrolestari with the AHP method showed that the chosen quantity with the weight of 0.279 and the chosen main alternative is to expand thecrumb rubber’s marketing and maximize the absorption of raw material with the weight of 0.163.Keywords : Rubber, Supply Chain, Added Value, SWOT, Analytical Hierarchy Process